2014
DOI: 10.1128/jvi.03726-13
|View full text |Cite
|
Sign up to set email alerts
|

Primary Human Macrophages Serve as Vehicles for Vaccinia Virus Replication and Dissemination

Abstract: Human monocytic and professional antigen-presenting cells have been reported only to exhibit abortive infections with vaccinia virus (VACV). We found that monocyte-derived macrophages (MDMs), including granulocyte macrophage colony-stimulating factor (GM-CSF)-polarized M1 and macrophage colony-stimulating factor (M-CSF)-polarized M2, but not human AB serumderived cells, were permissive to VACV replication. The titers of infectious virions in both cell-free supernatants and cellular lysates of infected M1 and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 86 publications
0
26
0
Order By: Relevance
“…In primary human macrophages in vitro , the cells are permissive to VACV infection and can be a vehicle for VACV replication and dissemination. These macrophages can produce extracellular enveloped virions for long-range VACV dissemination and form virion-associated structures contributing to cell-cell spread (36). Although the co-expression of CD11b and F4/80 has been often been used to identify macrophage-lineage cells, macrophages cannot be accurately distinguished from conventional DCs (CD11b + DC) and mo-DCs in skin.…”
Section: Discussionmentioning
confidence: 99%
“…In primary human macrophages in vitro , the cells are permissive to VACV infection and can be a vehicle for VACV replication and dissemination. These macrophages can produce extracellular enveloped virions for long-range VACV dissemination and form virion-associated structures contributing to cell-cell spread (36). Although the co-expression of CD11b and F4/80 has been often been used to identify macrophage-lineage cells, macrophages cannot be accurately distinguished from conventional DCs (CD11b + DC) and mo-DCs in skin.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses VACV (strain WR) was grown and titrated using 143B TK 2 cells, screened regularly for the presence of adventitious pathogens, as previously described (36). Recombinant VACV (rVACV) expressing GFP driven by the early/late p7.5 promoter (VACV-p7.5 GFP) or the late p11 promoter (VACV-p11 GFP) were described previously (31). For titrations of VACV from infected BMDC, cells were lysed at the time points indicated and titrated on 142B TK 2 cells as above.…”
Section: Cellsmentioning
confidence: 99%
“…The inability of late VACV promoter-driven Ag to stimulate T CD8+ responses has been correlated to an abortive in vitro infection of pAPC, in which late Ags are not produced and so direct presentation cannot occur (27)(28)(29)(30). However, some publications have indicated that VACV can replicate and spread following infection of APC (31), indicating either that all late genes required for productive replication can be produced within infected APC populations or that some APC populations may allow late VACV gene transcription. Therefore, the possibility exists that immunogenic late VACV Ags are primed by VACV-infected DC that directly present Ag.…”
Section: Introductionmentioning
confidence: 99%
“…Signals were sequentially collected using single fluorescence excitation and acquisition settings to avoid crossover. [45][46][47] Images were processed and analyzed using FV10-ASW 3.0 Viewer software (Olympus America, Center Valley, PA) or ImageJ 1.44p (NIH, Bethesda, MD).…”
Section: Confocal Microscopymentioning
confidence: 99%